The Effectiveness of Multimedia-Based Learning Models: Integration of Audiovisual Content and Interactive Games to Improve Understanding of Islamic Religious Education Values in Grade IV of SDN 1 Karangcegak Purbalingga - Irkham Auladi; Kholiyah Kholiyah; Adie Setiawan; Alief Budiyono (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
Islamic Religious Education (PAI) for fourth-grade students of SD Negeri 1 Karangcegak Purbalingga. The study used a qualitative descriptive approach with field research and a case study design. The subjects were fourth-grade PAI teachers, while data were collected through learning observations, in-depth interviews, and documentation. Data analysis was conducted interactively through the stages of data reduction, data presentation, and conclusion drawing. The results showed that the use of audiovisual content, such as animated videos and interactive presentations, was effective in increasing students' focus, learning interest, and contextual understanding of abstract PAI material. Meanwhile, the implementation of interactive digital quiz-based games was able to increase active participation, learning motivation, and students' ability to apply PAI values through a fun and reflective learning experience. The integration of the two media created more meaningful, student-centered learning and supported the strengthening of cognitive, affective, and psychomotor aspects. However, the implementation of this learning model still faces obstacles in the form of limited infrastructure and teacher readiness in managing digital media. Thus, it can be concluded that the multimedia-based learning model integrated with audiovisual content and interactive games is effective in improving the understanding of Islamic Religious Education values, with the note that it requires support from infrastructure and improving teacher competency so that its implementation is more optimal and sustainable.